PENGARUH BUDGETARY PARTICIPATION, INFORMATION ASYMMETRY, BUDGET EMPHASIS, DAN SELF ESTEEM TERHADAP BUDGETARY SLACK - Bangun, Nurainun; Andani, Kurniati W.; Sugianto, Wenny (Akuntansi Krida Wacana, 2012)
This research aims to evaluate whether budgetary participation, information asymmetry, budget emphasis, and self esteem affect budgetary slack. The validity and reliability test show that the questionarre is valid and reliable for the hypotheses test. Hypotheses are tested using linier regression and multiple regression. With the 95% level of significance, the result shows that budgetary participation, budget emphasis, and self esteem have the significant effect to budgetary slack, and have positive relationship. Information asymmetry doesnât have significant effect to budgetary slack. The multiple regression test shows that budgetary participation, information asymmetry, budget emphasis, and self esteem simultaneously have significant effect to budetary slack, and show the positive relationship. The next research is recommended to restrict the sample in certain industry, and adopt the other variable, like organization culture, ethic and reputation consideration, competition in company, social pressure, and risk aversion which can affect budgetary slack.Â Keywords: Budgetary Slack, Budgetary Participation, Information Asymmetry, Budget Emphasis, Self Esteem.